2019
DOI: 10.1021/acs.jpcc.9b06477
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Ion Dynamics of Nanoconfined LiBH4 in Silica

Abstract: The increasing demand for high capacity yet safe storage of renewable energy calls for the development of all-solid-state batteries. A major hurdle in this development is the identification of new suitable types of solid-state electrolytes. Nanoconfined lithium borohydride is a solid-state electrolyte candidate due to its high lithium-ion mobility at ambient temperatures. The origin of the high lithium-ion mobility is not fully understood, however. We studied nanocomposites of lithium borohydride and nanoporou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 69 publications
3
49
0
Order By: Relevance
“…Generally, such a confinement leads to a suppression of the long-range order in the confined material and, in many cases, to an enhancement of the mobility of anions and/or cations. Most of the studies in this direction have been performed on lithium borohydride infiltrated into nanoporous carbon or SiO 2 hosts [ 24 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. The characteristic feature of these nanocomposites is a coexistence of two distinct fractions of nanoconfined LiBH 4 .…”
Section: Effects Of Nanoconfinement On Dynamical Properties Of Hydmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, such a confinement leads to a suppression of the long-range order in the confined material and, in many cases, to an enhancement of the mobility of anions and/or cations. Most of the studies in this direction have been performed on lithium borohydride infiltrated into nanoporous carbon or SiO 2 hosts [ 24 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. The characteristic feature of these nanocomposites is a coexistence of two distinct fractions of nanoconfined LiBH 4 .…”
Section: Effects Of Nanoconfinement On Dynamical Properties Of Hydmentioning
confidence: 99%
“…Indeed, the narrow component of the 1 H NMR spectra has a width of about 1 kHz [ 24 , 92 , 94 ], and the reorientational motion alone cannot lead to such a narrowing (see Section 2 ). Experiments at various temperatures have revealed that the fraction of mobile spins increases with temperature [ 24 , 92 , 94 , 96 ]. This suggests that there is no fixed interface between the two fractions, which is consistent with the presence of broad continuous distributions of the jump rates [ 94 ].…”
Section: Effects Of Nanoconfinement On Dynamical Properties Of Hydmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 22 In this case, the improved Li-ion conductivity relies on the formation of a conductive interface, described by a core–shell model. 20 , 23 The fraction of LiBH 4 (the core) in direct contact with the oxide (the shell) forms an interfacial layer, featuring a Li-ion conductivity enhancement. The presence of different dynamics, due to the occurrence of slow and fast diffusivity of Li ions, has been detected for binary composites by 7 Li solid-state NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In the second method, the lithium salt is intimately mixed with a high surface area non-conducting oxide scaffold, such as SiO 2 or Al 2 O 3 . [35][36][37][38][39][40][41][42][43][44] Close contact can be achieved through nanoconnement by melt inltration of the metal hydride in the nanopores of the oxide, thereby forming a nanocomposite. 45 Interestingly, this method was originally used to improve hydrogen sorption properties of metal hydrides.…”
mentioning
confidence: 99%